2020
DOI: 10.1101/2020.06.25.171751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cheetah: a computational toolkit for cybergenetic control

Abstract: 1Advances in microscopy, microfluidics and optogenetics enable single cell monitoring and 2 environmental regulation and offer the means to control cellular phenotypes. The development 3 of such systems is challenging and often results in bespoke setups that hinder reproducibility. To 4 address this, we introduce Cheetah -a flexible computational toolkit that simplifies the integration 5 of real-time microscopy analysis with algorithms for cellular control. Central to the platform is an 6 image segmentation sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Several studies mention that the intestinal organoids contain similar cell proportions that those found in vivo [4,17,[42][43][44][45]. A study by Haber et al [46] reported the profiling of 53,193 (EnC), enterocyte progenitor (EnC-P), transit-amplifying cells (TA) (including on S and M cell-cycle phases), Paneth (PC), stem (SC), goblet (GC) and Tuft (TC) cells. Here, we extracted the cell population numbers of only the stem, TA and Paneth cells found in this study and inferred the initial proportion for the model.…”
Section: Model (I) Initial Conditionsmentioning
confidence: 87%
“…Several studies mention that the intestinal organoids contain similar cell proportions that those found in vivo [4,17,[42][43][44][45]. A study by Haber et al [46] reported the profiling of 53,193 (EnC), enterocyte progenitor (EnC-P), transit-amplifying cells (TA) (including on S and M cell-cycle phases), Paneth (PC), stem (SC), goblet (GC) and Tuft (TC) cells. Here, we extracted the cell population numbers of only the stem, TA and Paneth cells found in this study and inferred the initial proportion for the model.…”
Section: Model (I) Initial Conditionsmentioning
confidence: 87%
“…In future studies we aim to apply the strategy in-vivo, using the microfluidic experimental set-up already described in [19,21,37], which proved to be successful for control experiments involving both mammalian and bacterial cells. Several challenges will have to be addressed to enable a wider uptake of CBC:…”
Section: Future Developmentsmentioning
confidence: 99%
“…Recently, external feedback controllers have been exploited for controlling gene expression in living cells by means of microfluidics/microscopy or optogenetics platforms [19, 20, 21, 22, 23, 24, 25, 26, 27]. From a control theory standpoint, genetic networks are the processes to be controlled, while the controller is implemented on a computer.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, these solutions are difficult for non-experts to implement and cannot be easily transposed to a broad range of biological problems. More recently, several groups proposed Python and µManager-based software to develop cybergenetic experiments 16,17 , though these approaches remain specific to the control of gene expression in cells over time and do not meet all of the varied needs of cell biologists.…”
Section: Introductionmentioning
confidence: 99%